Mechanical plaque removal efficiency and antimicrobial property of Azadirachta Indica (NEEM) TWIG - Dizon, Anne L.; Santos, Mara Charlene L.; Dimanlig, Anna Marie C.
Background: Caries and periodontal disease are the most common preventable oral health diseases in the Philippines. The main means of prevention is through mechanical removal of plaque. It is known to many that aside from the toothbrush, chewing sticks such as neem twigs, have already been used as an alternative tool in many cultures for several years. Objectives: This study aimed to determine if neem twigs can effectively remove plaque mechanically and if it can reduce microorganisms associated with caries and gingival diseases in the oral cavity.Participants and Methods: Simple random sampling was done to select 11 participants from the dentistry proper students of the University of the Philippines College of Dentistry. The paired comparison experimental study design was used for this study. To determine if the neem twig extract is comparable to chlorhexidine in terms of reduction of the number of microorganisms in the oral cavity immediately after use, colony counts of the neem extract and chlorhexidine oral washings were compared with the colony counts of the baseline NSS oral washings. Plaque indices before and after using toothbrushes and neem twigs were also recorded to determine if neem twig is comparable to toothbrush in terms of mechanical plaque removal efficiency. Results: It was found that clinically, the toothbrush is more effective than the neem twig. However, results of the paired t-tests showed that statistically, there is no significant difference between the mechanical plaque removal of neem twig and toothbrush. In terms of the anti-microbial ability of the neem extract, it was found out that it differs statistically compared to chlorhexidine. Conclusion: The results provide evidence that neem twigs may serve as an alternative tool for tooth cleaning for those who cannot afford to by toothbrushes. This is due to its ability to remove plaque mechanically. Added to this capacity is its antimicrobial property.
Thesis--(Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Dental plaque; Tooth--Care and hygiene